What drives banks' geographic expansion? The role of locally non-diversifiable risk - Reint E. Gropp; Felix Noth; Ulrich Schüwer (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
We show that banks that are facing relatively high locally non-diversifiable risks in their home region expand more across states than banks that do not face such risks following branching deregulation in the United States during the 1990s and 2000s. Further, our evidence shows that these banks take into account the local risks in potential target regions: they expand more into counties where risks are relatively high and positively correlated with risks in their home region. This suggests that these banks do not only diversify but also build on their expertise in local risks when they expand into new regions.
Keywords: G21; G28; 330; banking; geographic expansion; deregulation; locally non-diversifiable risk; catastrophic risk